(3GdYjhfs - (3GdMSf Hf cQGeI GdLTej GdHjgbj, CHh SYjOs
(3ChdgG (B:s
(3gh cJGH jTJed Ydi PcQ GdaQb ef Cgd Gdghi hGNJdGa GdfGS ai GdCQGA hGdOjGfGJ s
(3BNQgG (B:s
(3hfHgfG ai cd eSCdI Edi dG GfgG CUM GdCOdI Hd gh hEf cGf UMjMkG aGdGOdI GdUMjMI deTGjNfG cKjQI s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3eUOQ GbJfGA GdCUd (B:s
(3GeHQhRjGfG (B(B 60) s
Keywords: (3GdadSaI hGdefWbs